2007
DOI: 10.1021/ic701607e
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry and Structure of Uranyl(VI) Hydroxo Dimer and Trimer Complexes in Aqueous Solution

Abstract: We studied the structure and stoichiometry of aqueous uranylVI hydroxo dimers and trimers by spectroscopic (EXAFS, FTIR, UV-vis) and quantum chemical (DFT) methods. FTIR and UV-vis spectroscopy were used for the speciation of uranyl complexes in aqueous solution. DFT calculations show that (UO2)2(OH)22+ has two bridging hydroxo groups with a U-U distance of 3.875 A. This result is in good agreement with EXAFS, where a U-U distance of 3.88 A was found. For the hydroxo trimer complex, DFT calculations show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 33 publications
7
77
0
Order By: Relevance
“…For both minerals no U-U backscattering was observed at acidic pH. The distance and CN at alkaline pH, S-2, are in line with the findings of Sylwester et al and can be explained by sorption of the aqueous uranyl dimer, (UO 2 ) 2 (OH) 2 , for which Tsushima et al (2007) determined a U-U distance of 3.875 Å . The significantly longer U-U distance of the acidic samples S-1 and S-3 are not in agreement with those of dimeric and trimeric aqueous complexes, but are in line with those of uranyl hydroxides such as b-hydroxide (4.22 Å ) (Taylor and Bannister, 1972), c-hydroxide (4.23 Å ) (Siegel et al, 1972) and the peroxide mineral studtite (4.21 Å ) (Burns and Hughes, 2003), all not very likely phases in our system.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…For both minerals no U-U backscattering was observed at acidic pH. The distance and CN at alkaline pH, S-2, are in line with the findings of Sylwester et al and can be explained by sorption of the aqueous uranyl dimer, (UO 2 ) 2 (OH) 2 , for which Tsushima et al (2007) determined a U-U distance of 3.875 Å . The significantly longer U-U distance of the acidic samples S-1 and S-3 are not in agreement with those of dimeric and trimeric aqueous complexes, but are in line with those of uranyl hydroxides such as b-hydroxide (4.22 Å ) (Taylor and Bannister, 1972), c-hydroxide (4.23 Å ) (Siegel et al, 1972) and the peroxide mineral studtite (4.21 Å ) (Burns and Hughes, 2003), all not very likely phases in our system.…”
Section: Resultssupporting
confidence: 89%
“…In the calculations with polymeric uranyl units, the most diffuse basis functions on uranium with the exponent of 0.005 (s-, p-, d-, and f-type functions) were omitted, as otherwise the geometry optimizations did not easily converge. Macak et al (2006) and Tsushima et al (2007) used a similar approach to calculate uranyl dimers and trimers, pointing out that this basis set without the diffuse functions had only a minor effect (less than 1 kJ/mol) on the total energies. All calculations were performed with the Gaussian03 (Frisch et al, 2004).…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…See also http://migrationdb.jaea.go.jp/tdb_e/d_page_e/d_0500_e.html. (Tsushima et al, 2007). c From Sverjensky et al (1997).…”
Section: Appendix Amentioning
confidence: 99%
“…The , and also shows a significantly difference in the intensity of the FT peak at ~2 Å (without phase shift). With the results of EXAFS fitting parameters as shown in Table 1 [35] crystal and uranyl hydroxo complex [36]. Compared with these previous results, it is suggested that the uranyl ion is surrounded by hydroxyl groups and water molecules but for the amidoxime group on the surface of the fiber.…”
Section: R-c Nh -Noh Uo Uo R-c Nh -No 2hmentioning
confidence: 76%